Contrast-enhanced ultrasound for multiple liver lesions after bone marrow transplant in a child with leukaemia: Multifocal focal nodular hyperplasia. (May 2019) - Verhagen, MV; Ciocarlie, O; Humphries, P; Watson, T
We present a case of a two-year-old girl in which liver lesions were characterised on contrast-enhanced ultrasound as multifocal focal nodular hyperplasia. This child had previously undergone haematopoietic stem cell transplantation for juvenile myelomonocytic leukaemia and was suspected to have hepatobiliary graft versus host disease. Liver biopsy was performed to confirm the unexpected focal nodular hyperplasia and look for concurrent graft versus host disease. Focal nodular hyperplasia was histologically confirmed on a background of diffuse liver damage in keeping with polypharmacotherapy, steatosis and sepsis. An element of graft versus host disease was not excluded but was not confidently shown in the sample of the lesion. This case report describes and illustrates how contrast-enhanced ultrasound may be of use to further assess hepatic lesions in a complex case of multifactorial hepatic pathology. Radiologists, haematologists and pathologists should be aware that multifocal focal nodular hyperplasia is part of the differential diagnosis of liver lesions in a child with liver damage due to complex disease and treatment. Biopsy remains the gold standard, if there is a concurrent clinical suspicion of graft versus host disease.